The Moon's classroom: Organizing a preferred center of students with pervasive developmental disorders. (Journal of Parents and Teachers, 2014)
In this article are explained  the organizational, methodological and curricular changes at a site over the past four years to meet the special educational needs of students with pervasive developmental disorders are explained.
Keywords: Pervasive developmental disorders; preferably center; draft courtyard; social skills; curriculum adaptation; education; experiences